Facile Synthesis of Holmium-Based Nanoparticles as a CT and MRI Dual-Modal Imaging for Cancer Diagnosis - Zhang, Tianqi; Deng, Mo; Zhang, Lei; Liu, Zerun; Liu, Yang; Song, Shuyan; Gong, Tingting; Yuan, Qinghai (Frontiers in Oncology, 2021)
The rapid development of medical imaging has boosted the abilities of modern medicine. As single modality imaging limits complex cancer diagnostics, dual-modal imaging has come into the spotlight in clinical settings. The rare earth element Holmium (Ho) has intrinsic paramagnetism and great x-ray attenuation due to its high atomic number. These features endow Ho with good potential to be a nanoprobe in combined x-ray computed tomography (CT) and T2-weighted magnetic resonance imaging (MRI). Herein, we present a facile strategy for preparing HoF3 nanoparticles (HoF3 NPs) with modification by PEG 4000. The functional PEG-HoF3 NPs have good water solubility, low cytotoxicity, and biocompatibility as a dual-modal contrast agent. Currently, there is limited systematic and intensive investigation of Ho-based nanomaterials for dual-modal imaging. Our PEG-HoF3 NPs provide a new direction to realize in vitro and vivo CT/MRI imaging, as well as validation of Ho-based nanomaterials will verify their potential for biomedical applications.